Physicochemical Studies of the Carbamate-CO/sub 2/-Solvent System - Prencipe, M.; Ishida, T. (Brooklyn College, 1977)
The formation of carbamate from CO/sub 2/ and the various amine solutions has been investigated for the purpose of elucidating the structure of the species generated in the reaction. The amine solutions used were 1 and 2 molar solutions of di-n-butylamine (DNBA) in triethylamine (TEA), pure DNBA and pure TEA. It has been found that the nonaqueous solvent participates in the formation of carbamate in 1 and 2M-DNBA/TEA solutions as a proton acceptor in DNBA-carbamate formation. However, due to the high concentration of the solutions and the basicities of the amines, a significant amount of DNBA which does not form the DNBA-carbamate anion is also found to be participating as a proton acceptor. Pure TEA absorbs only /sup 1///sub 60/ of the absorption by pure DNBA. The extent of TEA participation in the CO/sub 2/-absorption process other than as a proton acceptor in DNBA-carbamate is negligible. The formation of carbamic acid and zwitterion have been found unlikely. 7 tables, 15 figs.